Hadith #4872 - Sunan al-Nasa'i - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Maymun, Abu Hamza محمد بن ميمون المروزي أبو حمزة السكري; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan al-Nasa'i)
he was praying and a son a Marwan wanted to pass in front of him. He tried to stop him but he did not go back, so he hit him. The boy went the boy went out crying and went to Marwan and told him (what had happened). Marwan said to Abu Sa’eed: “Why did you hit your brother’s son?” He said: “I did not hit him, rater I hit the Saitan. I heard the Messenger of Allah say: ‘If one of you is praying and someone wants to pass in front of him, let him troy to stop him as much as he can, and i
Grade:

Hadith #5301 - Sunan al-Nasa'i - Abdullah bin 'Akaym عبد الله بن عكيم; Abdullah bin Abi Najih عبد الله بن أبي نجيح; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan al-Nasa'i)
The Messenger of Allah threw it away, and the people threw their rings away too. Then he took a ring of silver and he used to seal letters with it, but he did not wear it.
Grade:

Hadith #5669 - Sunan al-Nasa'i - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Abdullah bin 'Amr bin al-'Aas; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Mujahid bin Jabir مجاهد بن جبر; Yazid bin Abi Ziyad يزيد بن أبي زياد; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘The adulterer is not a believer at the moment when he is committing adultery, and the wine drinker is not a believer at the moment when he is drinking wine, and the thief is not a believer at the moment when he is stealing, and the robber is not a believer at the moment when he is robbing and people are looking on.'”
Grade:

Hadith #2372 - Sunan Abi Dawud - Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) had himself cupped when he was fasting. Abu Dawud said: Wuhaib b. Khalid narrated a similar tradition from Ayyub through a different chain of narrators. Ja’far b. Rabi’ah and Hisham, that is, Ibn Hassan, narrated a similar tradition from ‘Ikrimah on the authority of Ibn ‘Abbas.
Grade: Sahih

Hadith #2455 - Sunan Abi Dawud - Abdullah ibn al-Harith ibn Nawfal; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Umm Hani bint Abi Talib; Uthman bin Muhammad; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Abi Dawud)
When the Prophet (ﷺ) entered upon me, he would ask: Do you have food ? When we said: No, he would say: I am fasting. Waki’ added in his version: Another day when he entered upon us, we said: Messenger of Allah, some pudding (hair) has been presented to us and we have retained it for you. He said: Bring it to me. Talhah said: He fasted in the morning, but broke his fast (that day).
Grade: Sahih

Hadith #2646 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; ibn Umar; Yazid bin Abi Ziyad يزيد بن أبي زياد; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Ibn ‘Abbas said “When the verse “If there are twenty amongst you patient and persevering, they will vanquish two hundred” was revealed. It was heavy and troublesome for Muslims when Allaah prescribed for them that one (fighting Muslim) should not fly from ten (fighting Non-Muslims). Then a light commandment was revealed saying “For the present Allaah hath lightened your (task).” The narrator Abu Tawbah recited the verse to “they will vanquish two hundred.” When Allaah lightened t
Grade: Sahih

Hadith #3152 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Ahmad bin Hanbal أحمد بن حنبل; ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Uthman bin Muhammad; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Abi Dawud)
“of cotton”. The narrator said: Aisha was told that the people said that he was shrouded in two garments and one cloak. She replied: A cloak was brought but they returned it and did not shroud him in it.
Grade: Sahih

Hadith #4597 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Mujahid bin Jabir مجاهد بن جبر; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Abi Dawud)
Mu`awiyah b. Abi Sufiyan stood among us and said: Beware! The Apostle of Allah (ﷺ) stood among us and said: Beware! The people of the Book before were split up into seventy two sects, and this community will be split into seventy three: seventy two of them will go to Hell and one of them will go to Paradise, and it is the majority group. Ibn Yahya and `Amr added in their version : “ There will appear among my community people who will be dominated by desires like rabies which penetrates its
Grade: Hasan

Hadith #5221 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; ibn Umar; Yazid bin Abi Ziyad يزيد بن أبي زياد; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Ilyas ibn Dighfal said: I saw AbuNadrah kissing on the cheek of al-Hasan.
Grade: Sahih

Hadith #114 - Jami' al-Tirmidhi - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; Ali ibn Abi Talib; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Yazid bin Abi Ziyad يزيد بن أبي زياد; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Jami' al-Tirmidhi)
“I asked the Prophet about Al-Madhi. He said: “For Al-Madhi is Wudu, and for AI-Mani is Ghusl.”
Grade:

Hadith #528 - Jami' al-Tirmidhi - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; al-Bara' bin Azib bin al-Harith; Yazid bin Abi Ziyad يزيد بن أبي زياد (Jami' al-Tirmidhi)
Allah’s Messenger said: “It is a duty for the Muslims, that they perform Ghusl on Friday, and that each of them wear some of his family’s perfume. If he does not find any, then water is a perfume for him.”
Grade:

Hadith #529 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Yazid bin Abi Ziyad يزيد بن أبي زياد (Jami' al-Tirmidhi)
(Another route for the same chain) similar in meaning.
Grade:

Hadith #777 - Jami' al-Tirmidhi - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Ahmed bin Manay' أحمد بن منيع; ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Yazid bin Abi Ziyad يزيد بن أبي زياد (Jami' al-Tirmidhi)
“The Prophet was cupped somewhere between Makkah and Al-Madinah and he was fasting and in Ihram.”
Grade:

Hadith #832 - Jami' al-Tirmidhi - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; ibn Abbas; Muhammad bin 'Ali b. al-Hussain al-Baqir محمد بن علي بن الحسين بن علي ,الباقر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح; Yazid bin Abi Ziyad يزيد بن أبي زياد (Jami' al-Tirmidhi)
A man said: “Where should we begin our Hil (Ihram) O Messenger of Allah?” He said: “The people of Al-Madinah begin their Hil (Ihram) from Dhul-Hulaifah, the people from Ash-Sham from Al-Juhfah, and the people of Najd from Qarn.” And he (Ibn Umar) said: (“And they say:) “And the people of Yemen from Yalamlam.”
Grade:

Hadith #838 - Jami' al-Tirmidhi - Abdur Rahman bin Abi Na'm عبد الرحمن بن أبي نعم; Abu Sa'id al-Khudri; Ahmed bin Manay' أحمد بن منيع; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Yazid bin Abi Ziyad يزيد بن أبي زياد (Jami' al-Tirmidhi)
the Messenger of Allah said: “Five are Fawasiq which may be killed in the Haram: the mouse, the scorpion, the crow, the kite, and the barbed dog.”
Grade:

Hadith #932 - Jami' al-Tirmidhi - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; ibn Abbas; Mujahid bin Jabir مجاهد بن جبر; Yazid bin Abi Ziyad يزيد بن أبي زياد (Jami' al-Tirmidhi)
The Prophet was asked about whether Umrah was obligatory? He said: “No. But if you perform Umrah it is more virtuous.”
Grade:

Hadith #1668 - Jami' al-Tirmidhi - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; ibn Umar; Muhammad bin Yahya bin Abi 'Umar محمد بن يحيى بن أبي عمر العدني; Sufyan bin 'Uyaynah سفيان بن عيينة; Yazid bin Abi Ziyad يزيد بن أبي زياد (Jami' al-Tirmidhi)
“I heard Uthman while on the Minbar saying: ‘I did not inform you about a Hadith I had heard from the Messenger of Allah (ﷺ), out of dismay that you might part from me. Then it occurred to me that I should narrate to you so that one may choose from these matters accordingly. I heard the Messenger of Allah (ﷺ) saying: “(Ribat) Guarding the frontier for a day in Allah’s cause is beter in status than thousand days doing other than that.'” This Hadith is Hasan Sahih Gharib. Muhammad b
Grade:

Hadith #3872 - Jami' al-Tirmidhi - Abdullah ibn al-Harith ibn Nawfal; al-'Abbas ibn 'Abd al-Muttalib; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام; Yazid bin Abi Ziyad يزيد بن أبي زياد; Yusuf bin Musa bin Rashid al-Qatan يوسف بن موسى بن راشد القطان (Jami' al-Tirmidhi)
that ‘Ali mentioned the daughter of Abu Jahl (for marriage), and that reached the Prophet (ﷺ) so he said: “Indeed Fatimah is but a part of me, I am harmed by what harms her and I am uncomfortable by what makes her uncomfortable.”
Grade:

Hadith #3873 - Jami' al-Tirmidhi - Abdullah ibn al-Harith ibn Nawfal; al-Mtlb bin Abi Wda'h; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yazid bin Abi Ziyad يزيد بن أبي زياد (Jami' al-Tirmidhi)
that the Messenger of Allah (ﷺ) said to ‘Ali, Fatimah, Al-Hasan and Al-Husain: “I am at war with whoever makes war with you, and peace for whoever makes peace with you.”
Grade:

Hadith #282 - Sunan Ibn Majah - Aabad bin al-Walid bin Khalid عباد بن الوليد بن خالد الغبري; Abdullah bin Muhammad bin 'Aqil عبد الله بن محمد بن عقيل بن أبي طالب; Bakr bin Yahya bin Zban بكر بن يحيى بن زبان; Hban bin 'Ali al-Nzy حبان بن علي العنزي; Muhammad bin 'Aqil bin Abi Talib محمد بن عقيل بن أبي طالب; Muhammad bin al-Mu'ml bin al-Sbah محمد بن المؤمل بن الصباح; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“I was with the Messenger of Allah on a journey, and he said: ‘Is there any water?’ He performed ablution and wiped over his leather socks, then he joined the army and led them (in prayer).”
Grade:

Hadith #543 - Sunan Ibn Majah - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ali ibn Abi Talib; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“The Prophet (ﷺ) used to lead us in prayer, and he would take hold of his left hand with his right.”
Grade:

Hadith #1214 - Sunan Ibn Majah - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abdullah ibn al-Harith ibn Nawfal; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) saw some people riding on their animals in a funeral (procession). He said: ‘Do you not feel ashamed that the angels of Allah are walking on foot and you are riding?’”
Grade:

Hadith #1442 - Sunan Ibn Majah - Abdullah ibn al-Harith ibn Nawfal; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Sufyan bin 'Uyaynah سفيان بن عيينة; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“Whoever fasts three days in every month, that is fasting for a lifetime.” Then, in testimony of that, Allah revealed: “Whoever brings a good deed shall have ten time the like thereof to his credit.” So one day is equivalent to ten (in reward).
Grade:

Hadith #1538 - Sunan Ibn Majah - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; al-Hakam bin 'Utayba الحكم بن عتيبة; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
the Prophet said: “For every thirty cattle, Tabi or Tabi’ah and for every forty a Musinnah.”
Grade:

Hadith #1580 - Sunan Ibn Majah - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Muhammad bin 'Abdullah bin Numayr محمد بن عبد الله بن نمير; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
the Messenger of Allah said: “Marriage is part of my sunnah, and whoever does not follow my sunnah has nothing to do with me. Get married, for I will boast of your great numbers before the nations. Whoever has the means, let him get married, and whoever does not, then he should fast for it will diminish his desire.”
Grade:

Hadith #1752 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
the Messenger of Allah said: “The most hated of permissible things to Allah is divorce. “
Grade:

Hadith #2195 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Mujahid bin Jabir مجاهد بن جبر; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“May Allah (SWT) forgive Rafi’ bin Khadij. By Allah (SWT)! I have more knowledge of Ahadith than he does. Two men who had quarreled came to the Prophet (ﷺ) and he said: ‘If this is your situation, do not lease farms,’ and what Rafi’ bin khadij heard was ‘Do not lease farms.’ ”
Grade:

Hadith #2770 - Sunan Ibn Majah - Abdullah bin Numayr عبد الله بن نمير; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Jama' bin Shadad al-Maharbi جامع بن شداد المحاربي أبو صخرة; Tarq bin 'Abdullah; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
It was narrated from Abu Baddah bin ‘Asim, from his father, that the Prophet (ﷺ) granted permission for some shepherds to stone one day and to not stone (the next) day.
Grade:

Hadith #3045 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Mujahid bin Jabir مجاهد بن جبر; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“We ate food with the Messenger of Allah (ﷺ) in the mosque, meat that had been roasted. Then we wiped our hands on the pebbles and got up to perform prayer without performing ablution.”
Grade:

Hadith #3046 - Sunan Ibn Majah - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Aisha bint Abi Bakr; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Mujahid bin Jabir مجاهد بن جبر; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“A man came to the Prophet (ﷺ) and his voice trembled out of awe as he spoke to him. The Prophet said to him, “Be calm, for I am not a king. Verily, I am only the son of a woman who ate dried meat.”
Grade:

Hadith #3141 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ali bin Ms'hr علي بن مسهر; Sulaiman bin 'Amr bin al-Ahws سليمان بن عمرو بن الأحوص; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“Is anyone of you incapable of taking a water skin from the skin of her sacrifice each year?” Then she said: “The Messenger of Allah (ﷺ) forbade making Nabidh in (earthenware) jars, and in such and such, and such and such, except for vinegar.”
Grade:

Hadith #3144 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ali bin Ms'hr علي بن مسهر; Sulaiman bin 'Amr bin al-Ahws سليمان بن عمرو بن الأحوص; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“Cover your vessels, tie your water skins, extinguish your lamps and lock your doors, for Satan does not untie a water skin, open a door or uncover a vessel. If a person cannot find anything but a stick with which to cover his vessel and mention the Name of Allah, then let him do so. And the mouse could set fire to the house with its people inside.”
Grade:

Hadith #3145 - Sunan Ibn Majah - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Sulaiman bin 'Amr bin al-Ahws سليمان بن عمرو بن الأحوص; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) commanded us to cover our vessels, tie up our water skins and turn over our vessels.”
Grade:

Hadith #3197 - Sunan Ibn Majah - ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“I heard the Messenger of Allah (ﷺ) saying: ‘The cure for sciatica is the fat from the tail of a Bedouin sheep (or wild sheep), which should be melted and divided into three parts, one part to be taken each day on an empty stomach.’”
Grade:

Hadith #3206 - Sunan Ibn Majah - Abdur Rahman bin Abi Na'm عبد الرحمن بن أبي نعم; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“Intense fever is from the heat of Hell-fire, so cool it down with water.”
Grade:

Hadith #3227 - Sunan Ibn Majah - Abdur Rahman bin 'Abdullah bin Sabit عبد الرحمن بن عبد الله بن سابط; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ali bin Ms'hr علي بن مسهر; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“Ubayy bin Ka’b fell sick, and the Prophet (ﷺ) sent a doctor to him who cauterized him on his medical arm vein.”
Grade:

Hadith #3660 - Sunan Ibn Majah - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Sulaiman bin 'Amr bin al-Ahws سليمان بن عمرو بن الأحوص; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“I dislike (to see in a dream) a chain around the neck, but I like to see fetters on the feet, for fetters (represent) steadfastness in religion.”
Grade:

Hadith #3725 - Sunan Ibn Majah - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ali ibn Abi Talib; Hbyrh bin Yrym هبيرة بن يريم; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“People are like a hundred camels; you can hardly find one worth riding among them.”
Grade:

Hadith #3730 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ali bin Ms'hr علي بن مسهر; ibn Umar; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) stood up and addressed the people saying: ‘No, by Allah, I do not fear for you, O people, but I fear the attractions of this world that Allah brings forth for you.’ A man said to him: ‘O Messenger of Allah(ﷺ), does good bring forth evil?’ The Messenger of Allah (ﷺ) remained silent for a while, then he said: ‘What did you say?’ He said: ‘I said, does good bring forth evil?’ The Messenger of Allah (ﷺ) said: ‘Good does not bring forth anything
Grade:

Hadith #3772 - Sunan Ibn Majah - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Ali bin Ms'hr علي بن مسهر; ibn Umar; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“By the One in Whose Hand is my soul, this world will not pass away until a man will pass by a grave, and will roll on it and say: ‘Would that I were in the place of the occupant of this grave!’ And the reason for that will not be any religious motive, rather it will be because of calamity.”
Grade:

Hadith #4216 - Sunan Ibn Majah - Ali bin Salah bin Salah علي بن صالح بن صالح بن حي; Alqama bin Qays علقمة بن قيس بن عبد الله; ibn Mas'ud; Ibrahim al-Nakha'i إبراهيم النخعي; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Uthman bin Muhammad; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“The Messenger of Allah said: ‘Allah has taken me as a close friend (Khalil) as He took Ibrahim as a close friend. So my house and the house of Ibrahim will be opposite to one another on the Day of Resurrection, and ‘Abbas will be in between us, a believer between two close friends.'” (Maudu’)
Grade: